Validity of Neutrophil Gelatinase Associated Lipocaline as a Biomarker for Diagnosis of Children with Acute Pyelonephritis - Nickavar, Azar; Safaeian, Baranak; Valavi, Ehsan; Moradpour, Farhad (Urology Journal, 2016)
Purpose: Novel biomarkers have been investigated for various renal disorders, including urinary tract infection (UTI). The aim of this study was to assess whether urine neutrophil gelatinase associated lipocaline (NGAL), could represent a reliable biomarker for diagnosis and treatment of children with acute pyelonephritis (APN). Materials and Methods: A total of 37 children (32 females, 5 males) with APN were included in this prospective study. Urine NGAL was measured before and 5-7 days after antibiotic treatment in the UTI group, using ELISA kit and compared with 26 (8 females, 18 males) control group children admitted for other bacterial infections. Results: Mean age of the UTI group was 39 ± 28 months, compared to 43.6 ± 31.5 months for the control group with no statistically significant difference. Median urine NGAL level was significantly higher in patients with APN than the other subjects [0.48 (interquartile range (IQR): 0.15-0.72) vs. 0.065 (0.01-0.24), P = .001], and decreased significantly after antibiotic treatment (P = .002). Using a cutoff of 0.20 ng/mL, sensitivity and specificity of urine NGAL were 76% and 77% for prediction of APN, respectively. The area under the ROC curve (AUC) for urine NGAL was 0.75 (CI= 0.61-0.88), suggesting urine NGAL as a relatively good predictive biomarker of APN. Conclusion: Urine NGAL is a good biomarker for diagnosis and treatment monitoring of APN in children.